The Pattern of Communication and Teamwork among Operating Theatre Personnel in a State of a Developing Country - Olufemi Oyebanji Oyediran; Olamide Hope Olafare; Ifeoluwapo Oluwafunke Kolawole; Emmanuel Olufemi Ayandiran; Iyanuoluwa, Oreofe Ojo; Boluwaji Reuben Fajemilehin (Diponegoro University, 2022)
Background: Effective communication and teamwork is increasingly recognized as an important mechanism for enhancing the safety of healthcare. However, there is dearth of study on the pattern of communication among surgeons, nurses and anaesthetists in South Western part of Nigeria Purpose: This study assessed the patterns of communication and teamwork among operating theatre personnel and also identified barriers to communication and teamwork in the operating theatre in selected hospitals in Lagos State, Nigeria. Methods:  A descriptive research design was adopted and a convenience sampling technique was used to select 215 nurse and doctor respondents for the study. With a 53-item self-developed structured questionnaire, data were collected. Results were presented descriptively (frequency tables and bar charts), and inferential statistics (Chi-square) were used to test the hypotheses. Results: Results revealed that 41.9% of the respondents had a fair knowledge of communication and teamwork in the operating theatre. Respondents described their pattern of communication as  follows; the majority (99.5%) of the respondents communicate through written, spoken words or visual media, and 99.1% also communicate with other theatre personnel irrespective of their hierarchies. In addition, 90.7% reported that upward communication from patients to surgical team members is common in the theatre, while 87% submitted that they communicate through telephone conversations in this theatre. Individual bias, pressure to complete work, workload, poor leadership/lackadaisical attitudes and conflict of interest were identified as barriers to communication and teamwork in the operating theatre. Conclusion: The study concluded that the majority of theatre personnel lack adequate knowledge of communication and teamwork in the operating room. Hence, there is a need for periodic training for operating personnel to improve communication and teamwork, and surgical outcomes.